Dukungan Keluarga dan Depresi pada Penderita Hiv/Aids di Yogyakarta - Panji Andhika Pratama; Rr. Indahria Sulistyarini (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2012)
The aim of this study is to find out the relationship between family effect on the intention of depression on HIV/AIDS victim. The hypothesis of this research is there is a negative relationship between family support and of depression on HIV/AIDS victim. The subject of this research is 50 ODHA in Yogyakarta, 2 men and 48 woman. The scale for this research conducted by the reseacher based on the House aspect of family support (Smet, 1994), and adaptation of Beck scale is used to measure the depression aspect (1987), which is BDI II (Beck Depression Inventory II). Data analysist method on this research is using Spearman's non parametic corelation. The analysist shows r = -0.434 and p= 0.001 (p<0.05). The data shows the higher the family support, the lower of depression on the HIV/AIDS victim. And in reverse, the lower the family support, the higher of depression on the HIV/AIDS victim. Based on this research, we can see that family support contribute 18.9% in reducing the intention of depression on HIV/AIDS victim.Key Words : Family Intention, Depression